Finite element modeling of nanoindentation on C-S-H: Effect of pile-up and contact friction - Constantinides, Georgios; Sarris, Ernestos (My University, 2013)
In this paper we computationally study the indentation response of a rigid axisymmetric indenter on a semi-infinite elasto-plastic material of the Mohr-Coulomb type. The finite element method is used to quantify the effect of material properties (E, c,) and contact friction (μ) on the indentation response of C-S-H phases. The high E/c-ratio for both C-S-H phases, together with their cohesive-frictional behavior, leads to pile-up phenomena around the penetrated probe. The influence of all these parameters on the actual area of contact and its subsequent effect on commonly extracted quantities of the indentation test, namely indentation modulus (M) and indentation hardness (H), is investigated. It is shown that contact friction affects the contact area between the indenter and indented material and as a consequence interferes, to a certain extent, with the procedure for estimating elastic and plastic material properties. The effect is more pronounced for the hardness measurements.
Keywords: Calcium silicates; Finite element method; Friction; Tribology